Face‐Shared Octahedral Dimer In2O7S2 in the Non‐Centrosymmetric Barium Indiumsilicate Oxysulfide Ba2In2Si3O10S. Issue 12 (4th April 2016) - Guo, Wei‐Huan; Jiang, Xiao‐Ming; Liu, Bin‐Wen; Wu, Jia‐Wei; Li, Shu‐Fang; Zeng, Hui‐Yi; Guo, Guo‐Cong; Huang, Jin‐Shun
Abstract: The first indiumsilicate oxysulfide Ba2 In2 Si3 O10 S (1 ) was obtained by an alkali polychalcogenide flux method through a high‐temperature solid‐state reaction. It crystallizes in the non‐centrosymmetric space group Pca 21 (No. 29), with a = 23.060(6), b = 5.2954(6), c = 8.779(2) Å, and Z = 4. Its three‐dimensional (3D) framework is constructed from one‐dimensional (1D) infinite∞ 1 [In2 O7 S2/2 ] double octahedral chains bridged by corner‐sharing Si tetrahedral trimers [Si3 O10 ] 8–, yielding a 3D framework with the channels filled with Ba 2+ cations along the b direction. It is unprecedented in that the two distorted indium octahedra in1 face‐share to form a [In2 O7 S2 ] dimer in indium oxides and oxide chalcogenides. Abstract : The first indiumsilicate oxysulfide Ba2 In2 Si3 O10 S was obtained by an alkali polychalcogenide flux method. It is unprecedented in that the two distorted indium oxysulfide octahedra in this compound face‐share to form a [In2 O7 S2 ] dimer in indium oxides and sulfides.